Supplementation of 9-cis retinoic acid in the in vitro maturation medium increase blastocyst development rate and quality (Asian Journal of Medical and Biological Research, 2018)
The 9-cis retinoic acid (9-cisRA) enhances early embryonic development in both in vitro and in vivo conditions. This experiment was conducted to evaluate the effect of supplementation of 9-cisRA in the in vitro maturation (IVM) medium on embryo development efficiency and embryo quality. For this purpose, immature cumulus oocyte complexes (COC) collected from slaughterhouse derived bovine ovaries were matured in three different IVM media (control group, DMSO group and DMSO+RA group). In the control group, base IVM medium were used without supplementation of 9-cisRA and DMSO. In the DMSO group, base IVM medium was supplemented with 0.5 μl DMSO per ml IVM medium without 9-cisRA. In DMSO+RA group, base medium was supplemented with 5 nm 9-cisRA dissolved in 0.5 μl DMSO. Data were analyzed using one way ANOVA method and means were compared using Duncan’s multiple range test. Results showed that, supplementation of 9-cisRA in the maturation medium has no effect on embryonic development uptocleavage stage. However, blastocyst development rates (P>0.01), total blastomere number (P> 0.01), number of apoptotic blastomere per blastocyst (P>0.05) and percent of apoptotic blastomere per blastocyst (P>0.05) were significantly influences by 9-cisRA. In conclusion, 9-cisRA may be supplemented into the maturation medium for increasing bovinein vitro blastocyst development efficiency and blastocyst quality.Asian J. Med. Biol. Res. December 2017, 3(4): 516-520